2022
DOI: 10.55133/eji.290414
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-33 (IL-33) in children with active systemic lupus erythematosus: A cross-sectional study

Abstract: Interleukin-33 (IL-33) is a member of the IL-1 cytokine family and is associated with the development of different autoimmune diseases as systemic lupus erythematosus (SLE). So, the purpose of this cross-sectional study was to measure the serum IL-33 in children with SLE (c-SLE) in relation to their SLE disease activity index. This study was conducted upon 50 c-SLE patients in comparison to 50 normal matched children as a control group. Disease activity was assessed according to SLE Disease Activity Index (SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Of these, 13 were selected for fulltext examination based on the title and abstract, while four were disregarded because they lacked data or were review articles. Thus, nine publications satisfied our inclusion criteria [6][7][8][9][10][11][12][13][14] (Figure 1). The meta-analysis focused on five polymorphisms (rs1929992, rs1891385, rs7044343, rs1095498, and rs10975579).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 13 were selected for fulltext examination based on the title and abstract, while four were disregarded because they lacked data or were review articles. Thus, nine publications satisfied our inclusion criteria [6][7][8][9][10][11][12][13][14] (Figure 1). The meta-analysis focused on five polymorphisms (rs1929992, rs1891385, rs7044343, rs1095498, and rs10975579).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…5 Multiple studies have shown that IL-33 contributes to the pathophysiology of SLE by enhancing immune cell activation, cytokine release, and inflammation. [6][7][8][9][10][11][12][13][14] In response to IL-33, immune cells are known to release proinflammatory cytokines such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and interferon-γ (IFN-γ). 15 Additionally, IL-33 supports Th2 cell differentiation and activation as well as ILC2 activation, each associated with the emergence of autoimmune and allergic disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation